IMPROVING THE HYDRAULIC DRIVE OF THE MOTOR GRADER - V. S. Sherbakov; Yu. E. Ionova (Вестник СибАДИ, 2017)
The dependences of the turning of the front steerable wheels and the folding of the articulated frame off displacement of the rods of the hydraulic cylinders are considered. The machinery for synchronizing the turning of the front steerable wheels and folding the articulated frame is proposed. The hydraulic coefficient of proportionality between the working volumes of the negative feedback hydraulic motors and the displacement of the rods of the hydraulic cylinders turning the wheels and folding the articulated frame is obtained. The algorithm of motion the motor grader for a given trajectory is given.